4-O-Carboxymethylascochlorin Inhibits Expression Levels of on Inflammation-Related Cytokines and Matrix Metalloproteinase-9 Through NF–κB/MAPK/TLR4 Signaling Pathway in LPS-Activated RAW264.7 Cells - Park, Junyoung; Ha, Sun-Hyung; Abekura, Fukushi; Lim, Hakseong; Magae, Juni; Ha, Ki-Tae; Chung, Tae-Wook; Chang, Young-Chae; Lee, Young-Choon; Chung, Eunyong; Ku, Jiyeon; Kim, Cheorl-Ho (Frontiers in Pharmacology, 2019)
Toll-like receptor 4 (TLR4) and matrix metalloproteinase-9 (MMP-9) are known to play important roles in inflammatory diseases such as arteriosclerosis and plaque instability. The purpose of this study was to perform the effect of 4-O-carboxymethylascochlorin (AS-6) on MMP-9 expression in lipopolysaccharide (LPS)-induced murine macrophages and signaling pathway involved in its anti-inflammatory effect. Effect of AS-6 on MAPK/NF-κB/TLR4 signaling pathway in LPS-activated murine macrophages was examined using ELISA, Western blotting, reverse transcription polymerase chain reaction (RT-PCR) and fluorescence immunoassay. MMP-9 enzyme activity was examined by gelatin zymography. AS-6 significantly suppressed MMP-9 and MAPK/NF-κB expression levels in LPS-stimulated murine macrophages. Expression levels of iNOS, COX2, MMP-9, JNK, ERK, p38 phosphorylation, and NF-κB stimulated by LPS were also decreased by AS-6. Moreover, AS-6 suppressed TLR4 expression and dysregulated LPS-induced activators of transcription signaling pathway. The results of this study showed that AS-6 can inhibit LPS-stimulated inflammatory response by suppressing TLR4/MAPK/NF-κB signals, suggesting that AS-6 can be used to induce the stability of atherosclerotic plaque and prevent inflammatory diseases in an in vitro model.